2005
DOI: 10.1096/fj.04-2582fje
|View full text |Cite
|
Sign up to set email alerts
|

ABAD enhances Aβ‐induced cell stress via mitochondrial dysfunction

Abstract: Amyloid-beta peptide (Abeta) binding alcohol dehydrogenase (ABAD), an enzyme present in neuronal mitochondria, is a cofactor facilitating Abeta-induced cell stress. We hypothesized that ABAD provides a direct link between Abeta and cytotoxicity via mitochondrial oxidant stress. Neurons cultured from transgenic (Tg) mice with targeted overexpression of a mutant form of amyloid precursor protein and ABAD (Tg mAPP/ABAD) displayed spontaneous generation of hydrogen peroxide and superoxide anion, and decreased ATP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
222
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 44 publications
8
222
0
2
Order By: Relevance
“…In addition, we recently elucidated that the interaction of ABAD and Aβ caused mitochondrial dysfunction leading to neuronal apoptosis (Lustbader et al, 2004;Takuma et al, 2005). Interestingly, the present study demonstrated that OVX for 5 weeks increased neuronal ABAD level in the mouse hippocampus.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, we recently elucidated that the interaction of ABAD and Aβ caused mitochondrial dysfunction leading to neuronal apoptosis (Lustbader et al, 2004;Takuma et al, 2005). Interestingly, the present study demonstrated that OVX for 5 weeks increased neuronal ABAD level in the mouse hippocampus.…”
Section: Discussionsupporting
confidence: 52%
“…Unlike other respiratory complexes, complex IV has the capacity to retain partially reduced, unstable intermediates during electron transport, and therefore it is not considered a site of ROS production [47]. However, COX inhibition could lead to a backup of reduced complexes upstream in the respiratory chain, which has been proposed to increase ROS production [48][49][50].…”
Section: Complex IV Defects Oxidative Stress and Alzheimer's Diseasementioning
confidence: 99%
“…The proposed mechanisms of complex IV inhibition by Aβ include (i) blockage of mitochondrial import channels by APP to prevent the import of nuclear-encoded complex IV subunits [66], (ii) sequestration of heme by Aβ [67,68] and (iii) interaction between Aβ and Aβ-binding alcohol dehydrogenase (ABAD) [50,69]. The latter two mechanisms have been suggested to promote ROS production.…”
Section: Origins Of Complex IV Defects In Admentioning
confidence: 99%
“…There is compelling evidence that mitochondrial dysfunction is an early event in Alzheimer's and Parkinson's disease supporting claims that age-related mitochondrial dysfunction is an upstream event in many neurodegenerative disorders [18][19][20][21]. This is underscored in studies showing that amyloid precursor protein transgenic mice have decreased mitochondrial membrane potential, lowered ATP-levels and higher ROS levels, altered Bcl-xL/Bax ratio, reduced COX IV activity, and an overall decrease in mitochondrial respiratory function at a stage when there is no detectable level of amyloid-beta deposits in the brain [22].…”
Section: Introductionmentioning
confidence: 98%